Comparative Transcriptomics Reveals the Molecular Genetic Basis of Cave Adaptability in Sinocyclocheilus Fish Species - Zhao, Yincheng; Chen, Hongyu; Li, Chunqing; Chen, Shanyuan; Xiao, Heng (Frontiers in Ecology and Evolution, 2020)
Cavefish evolved a series of distinct survival mechanisms for adaptation to cave habitat. Such mechanisms include loss of eyesight and pigmentation, sensitive sensory organs, unique dietary preferences and predation behavior. Thus, it is of great interest to understand the mechanisms underlying these adaptability traits of troglobites. The teleost genus Sinocyclocheilus (Cypriniformes: Cyprinidae) is endemic to China and has more than 70 species reported (including over 30 cavefish species). High species diversity and diverse phenotypes make the Sinocyclocheilus as an outstanding model for studying speciation and adaptive evolution. In this study, we conducted a comparative transcriptomics study on the brain tissues of two Sinocyclocheilus species (surface-dwelling species - S. malacopterus and semi-cave-dwelling species - S. rhinocerous living in the same water body. A total of 425,188,768 clean reads were generated, which contributed to 102,839 Unigenes. Bioinformatic analysis revealed a total of 3,289 differentially expressed genes (DEGs) between two species Comparing to S. malacopterus, 2,598 and 691 DEGs were found to be respectively down-regulated and up-regulated in S. rhinocerous. Furthermore, it is also found tens of DEGs related to cave adaptability such as insulin secretion regulation (MafA, MafB, MafK, BRSK, and CDK16) and troglomorphic traits formation (CEP290, nmnat1, coasy, and pqbp1) in the cave-dwelling S. rhinocerous. Interestingly, most of the DEGs were found to be down-regulated in cavefish species and this trend of DEGs expression was confirmed through qPCR experiments. This study would provide an appropriate genetic basis for future studies on the formation of troglomorphic traits and adaptability characters of troglobites, and improve our understanding of mechanisms of cave adaptation.